Question
upstudy study bank question image url

EXERCISE 1.13 (a) Factorise: \( \begin{array}{lll}\text { (1) } 27 x^{3}-1 & \text { (2) } 8 x^{3}+1 & \text { (3) } 64 x^{3}-y^{3} \\ \text { (4) } 125-729 x^{3} & \text { (5) } a^{3} b^{3}-216 & \text { (6) } \\ \text { (60) } \\ \text { (7) } 8 a^{4}-64 a & \text { (8) }-x^{3}-27 & \text { (9) }\end{array} \)

Ask by Beck Hampton. in South Africa
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

Here are the factorizations: 1. \(27x^3 - 1 = (3x - 1)(9x^2 + 3x + 1)\) 2. \(8x^3 + 1 = (2x + 1)(4x^2 - 2x + 1)\) 3. \(64x^3 - y^3 = (4x - y)(16x^2 + 4xy + y^2)\) 4. \(125 - 729x^3 = (5 - 9x)(25 + 45x + 81x^2)\) 5. \(a^3b^3 - 216 = (ab - 6)(a^2b^2 + 6ab + 36)\) 6. \(8a^4 - 64a = 8a(a - 2)(a^2 + 2a + 4)\) 7. \(-x^3 - 27 = -(x + 3)(x^2 - 3x + 9)\)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

Extra Insights

Let's dive into these exercises and factor the expressions! 1. **27x³ - 1**: This is a difference of cubes, which can be factored using the formula \( a^3 - b^3 = (a - b)(a^2 + ab + b^2) \). Here, let \( a = 3x \) and \( b = 1 \): \[ 27x^3 - 1 = (3x - 1)(9x^2 + 3x + 1) \] 2. **8x³ + 1**: This is a sum of cubes, factored using \( a^3 + b^3 = (a + b)(a^2 - ab + b^2) \). Let \( a = 2x \) and \( b = 1 \): \[ 8x^3 + 1 = (2x + 1)(4x^2 - 2x + 1) \] 3. **64x³ - y³**: Again, this is a difference of cubes with \( a = 4x \) and \( b = y \): \[ 64x^3 - y^3 = (4x - y)(16x^2 + 4xy + y^2) \] 4. **125 - 729x³**: This expression can also be viewed as a difference of cubes. Let \( a = 5 \) and \( b = 9x \): \[ 125 - 729x^3 = (5 - 9x)(25 + 45x + 81x^2) \] 5. **a³b³ - 216**: Noticing that \( 216 = 6^3 \), we can express this as a difference of cubes with \( a = ab \) and \( b = 6 \): \[ a^3b^3 - 216 = (ab - 6)(a^2b^2 + 6ab + 36) \] 6. **8a⁴ - 64a**: This expression has a common factor of \( 8a \): \[ 8a^4 - 64a = 8a(a^3 - 8) = 8a(a - 2)(a^2 + 2a + 4) \] 7. **-x³ - 27**: This can be rewritten as \(- (x^3 + 27)\). Recognizing it as a sum of cubes with \( a = x \) and \( b = 3 \): \[ -x^3 - 27 = -(x + 3)(x^2 - 3x + 9) \] And voilà! Each expression has been factored accordingly! If you have more questions or need further help, feel free to ask!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy